Piotr Czyżewski’s “Alfurkan tatarski” (Wilno, 1616/1617) and its Authorship - Temčinas, Sergejus (Lietuvos istorijos studijos, 2023)
The article focuses on the textual characteristics of the Polish anti-Ta- tar pamphlet “Alfurkan tatarski” written by Piotr Czyżewski (Wilno, 1616/1617) and reveals its text being a compilation. There are at least four different indica- tions for this. They were a result of borrowing certain textual fragments from Matiasz Czyżewski’s earlier edition “Alkoran” (1616), which is considered lost. However, its long title describing the contents survives and can be safely com- pared to the extant text of Piotr Czyżewski’s “Alfurkan tatarski”. This comparison reveals thematic similarities between the two editions accompanied by identical wording which must be viewed as result of textual borrowing from the earlier edition into the later one. This collaborates well with A. Brückner’s comparison of the two editions (both were available to him in the early 20th century) which were reported to contain partially the same textual material. Traditionally the names of both authors are treated as pseudonyms of an un- known person who was recently identified with Józef Karcan (the printer of Piotr Czyżewski’s first edition of “Alfurkan tatarski”) or, alternatively, with Tomasz Pawłowski (the abbot of the Benedictine monastery in Old Trakai in ca 1597 – ca 1617). Nevertheless, the very nature of the revealed textual bor- rowings, accompanied by a significant rearrangement of the general struc ture, suggests that both editions have different authors. Since Matiasz and Piotr Czyżewski in their publications call themselves brothers and mention each other’s editions, they, contrary to the established tradition, must be con- sidered the actual authors of the respective printed books, and not fictitious pseudonyms.